The Effect of Liquid Organic Fertilizer from Tofu Factory and Local Microorganisms from Banana Stems of Ultisols - Siti Nurul Aidil Fitri; Adipati Napoleon; Agus Hermawan; Bakri Bakri; Karinda Dwi Paserena; Moch Aziz Pratama (Acta Solum, 2025)
Ultisol is a type of soil that requires processing before agricultural activities can be carried out due to its acidic pH and low nutrient content, necessitating proper treatment. Processing that can be done is by applying liquid organic fertilizer to Ultisol, as it provides nutrients according to plant needs and increases soil fertility. This study aims to understand the effect of the application of liquid organic fertilizer from tofu factory waste and local microorganisms from banana stems on N, P, K, and soil C/N ratio in Ultisols, and find out the best dosage of liquid organic fertilizer from tofu factory waste in increasing Soil N, P, K values ​​and C/N ratio in Ultisols. This research activity started from July to September 2024. This study employed a Completely Randomized Design (CRD) with 6 treatments and 4 replicates, resulting in 24 experimental units. The results showed that the liquid organic fertilizer treatment had a significant effect on available K levels and had no significant effect on total N, available P, and the C/N ratio of the soil in Ultisols. The best value obtained in the liquid organic fertilizer treatment was at a dose of 500 ml, which had an total N value of 0.19%, available P of 24.26 mg kg-1, available K of 1.60 cmol kg-1, and a soil C/N ratio of 15.27. Based on this research, it is suggested that to increase the availability of N, P, and K soil nutrients, it is necessary to provide liquid organic fertilizers with inorganic N, P, and K fertilizers.